A production process of alumina ceramic sheet

Through the sol-gel method, Fe and Al are combined, and gradient structure and special heat treatment technology are adopted, the problems of alumina ceramics are solved in high temperature, high pressure and corrosive environments, and their strength and resistance are significantly improved. Thermal shock and corrosion resistance.

CN119059801BActive Publication Date: 2025-02-07ZIBO DONGRUN CERAMIC TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411554884.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-07
Estimated Expiration
2044-11-04

AI Technical Summary

Technical Problem

Alumina ceramics exhibit brittleness, poor thermal shock stability and limitations in corrosive environments in high temperature, high pressure and corrosive environments.

Method used

Alumina ceramic sheet with gradient structure was prepared by the sol-gel method. The process involves sintering at high temperatures and high pressures and improving the crystallinity and chemical stability of the material through a special heat treatment procedure.

Benefits of technology

This process significantly improves the strength, thermal shock resistance and corrosion resistance of alumina ceramics, so that they maintain good complete form and excellent performance in high temperature, high pressure and corrosive environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application relates to the field of ceramic production, and in particular to a production process of an alumina ceramic sheet. In order to solve the problem of reduced performance of alumina ceramics in high temperature, high pressure, and corrosive environments in the prior art, the present application provides a production process of an alumina ceramic sheet. The alumina ceramic provided by the present application is compounded with Fe and Al by a sol-gel method, and can still maintain a relatively good intact form and excellent performance in a high temperature, high pressure, and corrosive environment, and has high strength, thermal shock resistance, and corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of ceramic production, and in particular to a production process of an alumina ceramic sheet. Background Art

[0002] Alumina ceramics are a high-performance inorganic non-metallic material, the main component of which is α-alumina, a crystalline form of aluminum oxide with a purity of more than 99.5%. In order to improve the performance of alumina ceramics, such as increasing sintering density, enhancing mechanical strength or optimizing thermal properties, appropriate amounts of additives are usually added to the raw materials. These additives can promote grain growth, reduce porosity, and thus improve the quality of the final product.

[0003] The preparation process of alumina ceramics can be roughly divided into three stages: powder preparation, molding and sintering. First, it is necessary to prepare fine and evenly distributed alumina powder, which can be prepared by chemical precipitation, sol-gel or hydrothermal synthesis, and then the powder is pressed into a green body of a predetermined shape by dry pressing, grouting or isostatic pressing. Finally, sintering is carried out at high temperature to make the particles adhere to each other and form a dense ceramic body.

[0004] Alumina ceramics have a variety of excellent properties, making them an ideal choice for many fields. First, alumina ceramics have extremely high hardness and wear resistance, and the Rockwell hardness can reach more than 90HRA, which is much higher than most metal materials. Secondly, it has excellent high temperature resistance and can be used for a long time at high temperatures above 1700℃ without significant performance degradation. In addition, alumina ceramics also have good chemical stability, can resist the erosion of most acid and alkali solutions, and are suitable for corrosive environments. At the same time, it also has high mechanical strength and bending strength, and can maintain structural integrity under high stress conditions. In the electronics industry, alumina ceramics are often used as substrate materials for integrated circuits because their good electrical insulation and thermal conductivity can effectively protect internal components from external interference. In the chemical industry, alumina ceramics are widely used in the manufacture of various corrosion-resistant equipment, such as reactors, pump and valve components, etc., thanks to their excellent resistance to most acid and alkali solutions. In the machinery manufacturing industry, alumina ceramics can also be used as tool coatings for precision tools, significantly improving the service life of workpieces. In addition, alumina ceramics also have important applications in aerospace, medical and energy fields.

[0005] Although alumina ceramics perform satisfactorily in high temperature, high pressure and highly corrosive environments, the existing technology still faces some problems in application. First, alumina ceramics are relatively brittle. Although they have excellent hardness and wear resistance, their fracture toughness is low, and cracks are prone to propagate, leading to material damage. This brittleness not only affects its use under dynamic load conditions, but also limits the design freedom to a certain extent. In high temperature and high pressure environments, this brittleness problem is more prominent because the material is more likely to break when subjected to impact or vibration. Secondly, alumina ceramics have poor thermal shock stability. When the material is suddenly exposed to drastic temperature changes, the thermal stress generated inside may cause cracks to form and propagate, eventually causing material failure. In high temperature and high pressure environments, the impact of this thermal stress is particularly significant. Finally, alumina ceramics still have limitations in corrosive environments. Although it has good resistance to most acid and alkali solutions, it still dissolves or corrodes slowly, which limits its application in these extreme environments. Summary of the invention

[0006] In order to solve the problem in the prior art that the performance of alumina ceramics is reduced in high temperature, high pressure and corrosive environments, the present application provides a production process for alumina ceramic sheets. The alumina ceramics provided by the present application are composited with Fe and Al by a sol-gel method. In a high temperature, high pressure and corrosive environment, they can still maintain a relatively good intact shape and excellent performance, and have high strength, thermal shock resistance and corrosion resistance.

[0007] The present application provides a production process of an alumina ceramic sheet, comprising the following steps:

[0008] S1. Add AlCl3·6H2O to water, stir the solution at room temperature until it is completely dissolved, add ethanol to the solution, and raise the temperature to 65-75°C, then add hexadecyltrimethylammonium bromide while maintaining the temperature, react for 5-10 minutes, then add sodium borohydride to the solution for later use;

[0009] S2, after the S1 solution becomes transparent, heat it to 85-95°C, maintain it for 20-30 minutes, dry it to obtain a white powder, wash it with water and ethanol, and then dry it for later use;

[0010] S3, adding FeSO4·6H2O into water, stirring the solution at room temperature to make it uniform, and then adding it to the solution prepared in S1 to obtain solutions with iron contents of 2%, 4% and 6%, respectively. After the solution becomes transparent, the temperature is raised to 90-95°C and maintained for 20-30 minutes. The solution becomes a gel and is dried to obtain a white powder, which is washed with water and ethanol and then dried for later use;

[0011] S4, the powder obtained in S2, the powder with an iron content of 2% obtained in S3, the powder with an iron content of 4% obtained in S3, and the powder with an iron content of 6% obtained in S3 are successively spread into a mold from bottom to top, and the heating furnace is preheated to 700-750° C., and sintered for 1-1.5 hours to obtain a pre-sintered product;

[0012] S5, placing the aluminum alloy on the pre-sintered product obtained in S4, and then sending it into the heating furnace again, raising the temperature to 900-950° C., maintaining it for 30-50 minutes, taking it out and cooling it to room temperature;

[0013] S6. Preheat the heating furnace to 1000-1100°C, send the product obtained in S5 into the heating furnace for sintering for 2-3h, take it out and cool it to room temperature, send it into the heating furnace again, slowly heat it to 600-680°C at a rate of 5°C / min and keep it for 4-5h, then slowly cool it to room temperature at a rate of 5°C / min to obtain alumina ceramics.

[0014] Furthermore, in step S1, the mass ratio of AlCl3·6H2O, ethanol, hexadecyltrimethylammonium bromide and sodium borohydride is 12:7-8:0.1-0.2:0.1-0.2.

[0015] Furthermore, the hexadecyltrimethylammonium bromide and sodium borohydride in step S1 are aqueous solutions with a concentration of 0.02-0.05 g / mL.

[0016] Furthermore, in step S4, the mass ratio of the powder obtained in S2, the powder with an iron content of 2% obtained in S3, the powder with an iron content of 4% obtained in S3, and the powder with an iron content of 6% obtained in S3 is 8:2-2.5:0.5-1:0.5-1.

[0017] Furthermore, the aluminum alloy is one or more of 5A05, 5052, 5083, and 5005.

[0018] Furthermore, the mass ratio of the aluminum alloy in step S5 to the pre-sintered product obtained in step S4 is 3-5:3.

[0019] Furthermore, in step S5, the aluminum alloy is pretreated by cleaning with acetone at room temperature and vacuuming at 10 -3 -10 -4 Pa, degas for 1-2h in an environment with a temperature of 120-150℃.

[0020] The beneficial effects of this application are:

[0021] AlCl3·6H2O dissolves in water to form Al 3+ions, which is the basis for the preparation of alumina precursors. The addition of ethanol helps to reduce the surface tension of the solution, promotes uniform mixing, and also helps the subsequent sol-gel process. Hexadecyltrimethylammonium bromide is a cationic surfactant that can be adsorbed on Al 3+ ions, forming a stable micelle structure to prevent Al 3+ ions to obtain a uniform precursor solution. FeSO4·6H2O dissolves in water to form Fe 2+ ions, which will react with Al 3+ The ions are mixed to form a composite precursor, and the iron content in the final product can be adjusted by controlling the amount of FeSO4·6H2O added.

[0022] The stacking of powders with different iron contents helps to form a gradient structure during the sintering process and improve the overall performance of the material. The gradient setting can form a performance transition from the surface to the inside, so that the material has different mechanical properties in different areas. The surface area can enhance hardness and wear resistance through high Fe content, while the internal area maintains high toughness and crack resistance. By stacking powders with different iron contents, a continuous performance gradient can be formed inside the material. This gradient distribution allows the material to gradually transfer and disperse stress when subjected to external forces, rather than concentrating at a certain point, effectively dispersing stress and reducing stress concentration points, thereby improving the overall strength and crack resistance of the material. The gradient structure can reduce the thermal stress generated by the material when the temperature changes and improve the thermal shock stability of the material. Through the gradient setting, the crack propagation path inside the material becomes more complicated, and the crack is not easy to propagate along a straight line, thereby slowing down the crack propagation speed. Areas with different iron contents have different thermal expansion coefficients. Through the gradient setting, the thermal expansion coefficient can be gradually transitioned from the surface to the inside, reducing the thermal stress caused by temperature changes. The gradient setting also makes the components in the material evenly distributed, reduces the phenomenon of excessive local concentration differences, and improves the uniformity and consistency of the material.

[0023] 5A05, 5052, 5083, and 5005 aluminum alloys are selected. These alloys have good thermal stability and mechanical properties, and can form a good bonding interface with alumina ceramics. After pre-sintering, the aluminum alloy fills the pores therein, significantly improving the mechanical properties and corrosion resistance of the ceramics. The presence of Mg in the aluminum alloy can significantly reduce the surface tension of the Al liquid and the surface energy between the Al liquid and alumina, and reduce the formation of harmful interfacial reaction phases, which may reduce the mechanical strength and corrosion resistance of the composite material. Reducing the surface energy allows the Al liquid to better fill the pores and form a dense composite material. In the composite material, the Al liquid forms a three-dimensional interpenetrating network structure, which can effectively disperse and absorb external forces, improve the strength and toughness of the composite material, and thus improve the overall density and mechanical properties of the composite material.

[0024] The scheme of the present application performs a special heat treatment on alumina ceramics, pre-sintering at 700-750°C to make the gel initially solidified, but leaving gaps to ensure the subsequent doping of aluminum alloys, and heat treatment at 1000-1100°C for a long time to promote the amorphous phase in the material to gradually transform into a crystalline phase. This process can improve the crystallinity of the material and reduce grain boundary defects such as vacancies and dislocations, thereby improving the mechanical properties and chemical stability of the material. After sintering, it is quickly cooled at room temperature to fix the grain structure in the material and reduce the accumulation of impurities at the grain boundaries, thereby improving the mechanical properties and corrosion resistance of the material, and further improving the compressive strength of the material. The grain structure is fixed by rapid cooling and the softening at the grain boundaries is reduced. After sintering, the temperature is slowly raised to 600-680°C at a rate of 5°C / min and maintained for 4-5h, and then cooled to room temperature at the same rate, which can improve the initial compressive strength of the material, reduce defects at the grain boundaries, and improve the bonding force of the grains. Long-term heat treatment can also eliminate residual stress inside the material and improve the thermal shock stability of the material. Through the above-mentioned heat treatment, the bending strength of the material can also be improved, and the toughness and crack resistance of the material can be enhanced. DETAILED DESCRIPTION

[0025] The technical scheme of the present invention and its effects are further described below by specific examples. The following examples are only used to illustrate the content of the present invention and are not used to limit the protection scope of the present invention. Simple changes made to the present invention by applying the concept of the present invention are all within the scope of the protection claimed by the present invention.

[0026] The equipment used in the preparation method of the present invention can be the well-known equipment in the art. The raw materials used in the present invention are commercially available unless otherwise specified.

[0027] Example 1

[0028] S1. Add 12 g of AlCl3·6H2O to 100 mL of water, stir the solution with a magnetic stirrer at room temperature for 10 min, add 10 mL of ethanol to the solution, and raise the temperature to 70°C, then add 5 mL of 0.02 g / mL hexadecyltrimethylammonium bromide solution while maintaining the temperature, react for 5 minutes, then add 5 mL of 0.02 g / mL sodium borohydride solution to the solution for later use;

[0029] S2, after the S1 solution becomes transparent, take a portion and heat it to 90°C, keep it for 30 minutes, and dry it to obtain a white powder, wash it with water and ethanol, and then dry it for later use;

[0030] S3, add 14g FeSO4·6H2O to 100mL water, stir the solution with a magnetic stirrer at room temperature for 10min, then add to the solution prepared in S1 to obtain solutions with iron contents of 2%, 4% and 6%, respectively. After the solution becomes transparent, raise the temperature to 90°C and keep for 30min. After drying, obtain white powder, wash with water and ethanol, and dry for later use;

[0031] S4, the powder obtained in S2, the powder with an iron content of 2% obtained in S3, the powder with an iron content of 4% obtained in S3, and the powder with an iron content of 6% obtained in S3 are successively spread into a mold in a bottom-to-top order with a mass ratio of 8:2:1:1, and the heating furnace is preheated to 700°C and sintered for 1 hour to obtain a pre-sintered product;

[0032] S5 and 5A05 aluminum alloys were pretreated and cleaned with acetone at room temperature. -4 Pa, degassing in an environment with a temperature of 120°C for 1h, placing 5A05 aluminum alloy on the pre-sintered product obtained in S4 with a mass ratio of 1:1, and then sending it into the heating furnace again, raising the temperature to 900°C, maintaining it for 30min, taking it out and cooling it to room temperature;

[0033] S6. Preheat the heating furnace to 1000°C, send the product obtained in S5 into the heating furnace for sintering for 2 hours, take it out and cool it to room temperature, send it into the heating furnace again, slowly heat it to 600°C at a rate of 5°C / min and keep it for 5 hours, then slowly cool it to room temperature at a rate of 5°C / min to obtain an alumina ceramic sheet.

[0034] Example 2

[0035] S1. Add 12 g of AlCl3·6H2O to 100 mL of water, stir the solution with a magnetic stirrer at room temperature for 10 min, add 9 mL of ethanol to the solution, and raise the temperature to 65°C, then add 10 mL of 0.02 g / mL hexadecyltrimethylammonium bromide solution while maintaining the temperature, react for 10 minutes, then add 10 mL of 0.02 g / mL sodium borohydride solution to the solution for later use;

[0036] S2, after the S1 solution becomes transparent, take a portion and heat it to 85°C, keep it for 20 minutes, and dry it to obtain a white powder, wash it with water and ethanol, and then dry it for later use;

[0037] S3, add 14g FeSO4·6H2O to 100mL water, stir the solution with a magnetic stirrer at room temperature for 10min, then add to the solution prepared in S1 to obtain solutions with iron contents of 2%, 4% and 6%, respectively. After the solution becomes transparent, raise the temperature to 95°C and keep for 20min. After drying, obtain white powder, wash with water and ethanol, and dry for later use;

[0038] S4, the powder obtained in S2, the powder with an iron content of 2% obtained in S3, the powder with an iron content of 4% obtained in S3, and the powder with an iron content of 6% obtained in S3 are successively spread into a mold in a bottom-to-top order, with a mass ratio of 8:2.5:0.5:0.5, and the heating furnace is preheated to 750°C and sintered for 1.5 hours to obtain a pre-sintered product;

[0039] S5, 5052 aluminum alloy was pretreated and cleaned with acetone at room temperature and vacuumed to 10 -3 Pa, degassing in an environment with a temperature of 150°C for 2h, placing the 5052 aluminum alloy on the pre-sintered product obtained in S4 with a mass ratio of 5:3, and then sending it into the heating furnace again, raising the temperature to 950°C, maintaining it for 50min, and cooling it to room temperature after taking it out;

[0040] S6. Preheat the heating furnace to 1100°C, send the product obtained in S5 into the heating furnace for sintering for 3 hours, take it out and cool it to room temperature, send it into the heating furnace again, slowly heat it to 680°C at a rate of 5°C / min and keep it for 4 hours, then slowly cool it to room temperature at a rate of 5°C / min to obtain an alumina ceramic sheet.

[0041] Example 3

[0042] S1. Add 12 g of AlCl3·6H2O to 100 mL of water, stir the solution with a magnetic stirrer at room temperature for 10 min, add 10 mL of ethanol to the solution, and raise the temperature to 75°C, then add 8 mL of 0.02 g / mL hexadecyltrimethylammonium bromide solution while maintaining the temperature, react for 5 minutes, then add 8 mL of 0.02 g / mL sodium borohydride solution to the solution for later use;

[0043] S2, after the S1 solution becomes transparent, take a portion and heat it to 95°C, keep it for 25 minutes, and dry it to obtain a white powder, wash it with water and ethanol, and then dry it for later use;

[0044] S3, add 14g FeSO4·6H2O to 100mL water, stir the solution with a magnetic stirrer at room temperature for 10min, then add to the solution prepared in S1 to obtain solutions with iron contents of 2%, 4% and 6%, respectively. After the solution becomes transparent, raise the temperature to 95°C and keep for 25min. After drying, obtain white powder, wash with water and ethanol, and dry for later use;

[0045] S4, the powder obtained in S2, the powder with 2% iron content obtained in S3, the powder with 4% iron content obtained in S3, and the powder with 6% iron content obtained in S3 are successively spread into the mold in the order from bottom to top, with a mass ratio of 8:2.2:0.7:0.7, the heating furnace is preheated to 720°C, and sintered for 1.3h to obtain a pre-sintered product;

[0046] S5, 5083 aluminum alloy were pretreated, cleaned with acetone at room temperature, and vacuumed at 10 -4 Pa, degassing in an environment with a temperature of 130°C for 1.5h, placing the 5083 aluminum alloy on the pre-sintered product obtained in S4 with a mass ratio of 4:3, and then sending it into the heating furnace again, raising the temperature to 920°C, maintaining it for 40min, and cooling it to room temperature after taking it out;

[0047] S6. Preheat the heating furnace to 1050°C, send the product obtained in S5 into the heating furnace for sintering for 2.5 hours, take it out and cool it to room temperature, send it into the heating furnace again, slowly increase the temperature to 650°C at a rate of 5°C / min and keep it for 4.5 hours, then slowly decrease the temperature to room temperature at a rate of 5°C / min to obtain an alumina ceramic sheet.

[0048] Comparative Example 1

[0049] S1. Add 12 g of AlCl3·6H2O to 100 mL of water, stir the solution with a magnetic stirrer at room temperature for 10 min, add 10 mL of ethanol to the solution, and raise the temperature to 70°C, then add 5 mL of 0.02 g / mL hexadecyltrimethylammonium bromide solution while maintaining the temperature, react for 5 minutes, then add 5 mL of 0.02 g / mL sodium borohydride solution to the solution for later use;

[0050] S2, after the S1 solution becomes transparent, take a portion and heat it to 90°C, keep it for 30 minutes, and dry it to obtain a white powder, wash it with water and ethanol, and then dry it for later use;

[0051] S3, add 14g FeSO4·6H2O to 100mL water, stir the solution with a magnetic stirrer at room temperature for 10min, then add to the solution prepared in S1 to obtain solutions with iron contents of 2%, 4% and 6%, respectively. After the solution becomes transparent, raise the temperature to 90°C and keep for 30min. After drying, obtain white powder, wash with water and ethanol, and dry for later use;

[0052] S4, the powder obtained in S2, the powder with an iron content of 2% obtained in S3, the powder with an iron content of 4% obtained in S3, and the powder with an iron content of 6% obtained in S3 are successively spread into a mold in a bottom-to-top order with a mass ratio of 8:2:1:1, and the heating furnace is preheated to 700°C and sintered for 1 hour to obtain a pre-sintered product;

[0053] S5 and 5A05 aluminum alloys were pretreated and cleaned with acetone at room temperature. -4 Pa, degassing in an environment with a temperature of 120°C for 1h, placing 5A05 aluminum alloy on the pre-sintered product obtained in S4 with a mass ratio of 1:1, and then sending it into the heating furnace again, raising the temperature to 900°C, maintaining it for 30min, taking it out and cooling it to room temperature;

[0054] S6, preheating the heating furnace to 1000°C, sending the product obtained in S5 into the heating furnace for sintering for 2 hours, taking it out and cooling it to room temperature to obtain an alumina ceramic sheet.

[0055] Comparative Example 2

[0056] S1. Add 12 g of AlCl3·6H2O to 100 mL of water, stir the solution with a magnetic stirrer at room temperature for 10 min, add 10 mL of ethanol to the solution, and raise the temperature to 70°C, then add 5 mL of 0.02 g / mL hexadecyltrimethylammonium bromide solution while maintaining the temperature, react for 5 minutes, then add 5 mL of 0.02 g / mL sodium borohydride solution to the solution for later use;

[0057] S2, after the S1 solution becomes transparent, take a portion and heat it to 90°C, keep it for 30 minutes, and dry it to obtain a white powder, wash it with water and ethanol, and then dry it for later use;

[0058] S3, add 14g FeSO4·6H2O to 100mL water, stir the solution with a magnetic stirrer at room temperature for 10min, then add to the solution prepared in S1 to obtain solutions with iron contents of 2%, 4% and 6%, respectively. After the solution becomes transparent, raise the temperature to 90°C and keep for 30min. After drying, obtain white powder, wash with water and ethanol, and dry for later use;

[0059] S4, the powder obtained in S2, the powder with an iron content of 2% obtained in S3, the powder with an iron content of 4% obtained in S3, and the powder with an iron content of 6% obtained in S3 are successively spread into a mold in a bottom-to-top order with a mass ratio of 8:2:1:1, and the heating furnace is preheated to 700°C and sintered for 1 hour to obtain a pre-sintered product;

[0060] S5, preheat the heating furnace to 1000°C, send the product obtained in S4 into the heating furnace for sintering for 2 hours, take it out and cool it to room temperature, send it into the heating furnace again, slowly heat it to 600°C at a rate of 5°C / min and keep it for 5 hours, then slowly cool it to room temperature at a rate of 5°C / min to obtain an alumina ceramic sheet.

[0061] Comparative Example 3

[0062] S1. Add 12 g of AlCl3·6H2O to 100 mL of water, stir the solution with a magnetic stirrer at room temperature for 10 min, add 10 mL of ethanol to the solution, and raise the temperature to 70°C, then add 5 mL of 0.02 g / mL hexadecyltrimethylammonium bromide solution while maintaining the temperature, react for 5 minutes, then add 5 mL of 0.02 g / mL sodium borohydride solution to the solution for later use;

[0063] S2, after the S1 solution becomes transparent, take a portion and heat it to 90°C, keep it for 30 minutes, and dry it to obtain a white powder, wash it with water and ethanol, and then dry it for later use;

[0064] S3, add 14g FeSO4·6H2O to 100mL water, stir the solution with a magnetic stirrer at room temperature for 10min, then add it to the solution prepared in S1 to obtain a solution with an iron content of 6%. After the solution becomes transparent, raise the temperature to 90°C and maintain for 30min. After drying, obtain a white powder, wash with water and ethanol, and then dry for use;

[0065] S4, the powder obtained in S2 and the powder with an iron content of 6% obtained in S3 are spread into the mold in a bottom-to-top order with a mass ratio of 2:1, the heating furnace is preheated to 700°C, and sintered for 1 hour to obtain a pre-sintered product;

[0066] S5 and 5A05 aluminum alloys were pretreated and cleaned with acetone at room temperature. -4 Pa, degassing in an environment with a temperature of 120°C for 1h, placing 5A05 aluminum alloy on the pre-sintered product obtained in S4 with a mass ratio of 1:1, and then sending it into the heating furnace again, raising the temperature to 900°C, maintaining it for 30min, taking it out and cooling it to room temperature;

[0067] S6. Preheat the heating furnace to 1000°C, send the product obtained in S5 into the heating furnace for sintering for 2 hours, take it out and cool it to room temperature, send it into the heating furnace again, slowly heat it to 600°C at a rate of 5°C / min and keep it for 5 hours, then slowly cool it to room temperature at a rate of 5°C / min to obtain an alumina ceramic sheet.

[0068] Comparative Example 4

[0069] S1. Add 12 g of AlCl3·6H2O to 100 mL of water, stir the solution with a magnetic stirrer at room temperature for 10 min, add 10 mL of ethanol to the solution, and raise the temperature to 70°C, then add 5 mL of 0.02 g / mL hexadecyltrimethylammonium bromide solution while maintaining the temperature, react for 5 minutes, then add 5 mL of 0.02 g / mL sodium borohydride solution to the solution for later use;

[0070] S2, after the S1 solution becomes transparent, take a portion and heat it to 90°C, keep it for 30 minutes, and dry it to obtain a white powder, wash it with water and ethanol, and then dry it for later use;

[0071] S3, spreading the powder obtained in S2 into a mold, preheating the heating furnace to 700°C, and sintering for 1 hour to obtain a pre-sintered product;

[0072] S4 and 5A05 aluminum alloys were pretreated and cleaned with acetone at room temperature. -4 Pa, degassing in an environment with a temperature of 120°C for 1h, placing 5A05 aluminum alloy on the pre-sintered product obtained in S3 with a mass ratio of 1:1, and then sending it into the heating furnace again, raising the temperature to 900°C, maintaining it for 30min, taking it out and cooling it to room temperature;

[0073] S5, preheat the heating furnace to 1000°C, send the product obtained in S4 into the heating furnace for sintering for 2 hours, take it out and cool it to room temperature, send it into the heating furnace again, slowly heat it to 600°C at a rate of 5°C / min and keep it for 5 hours, then slowly cool it to room temperature at a rate of 5°C / min to obtain an alumina ceramic sheet.

[0074] The alumina ceramic sheets obtained in the examples and comparative examples were cut into samples of 7 mm × 15 mm. The samples were tested by load sensors with an initial load of 0.5 N. The load was increased at a constant compression speed of 100 mm / min at the center of the sample until damage occurred. The load at which the fracture occurred was recorded. The corrosion resistance test was performed by boiling the samples in 20% sulfuric acid solution for 1 hour, and the percentage of mass reduction compared to the mass before corrosion was calculated.

[0075] Thermal shock resistance measurement: Wash the sample, dry it in a heating box at 120℃±10℃, cool it naturally to room temperature, and then put it in a heating furnace at 900±10℃ for 10 minutes. Take out the sample and place it on an asbestos board, cool it naturally to room temperature under normal test atmospheric conditions, and then put the sample into a heating furnace at the specified temperature. Repeat the test 10 times, immerse it in a 1% fuchsin solution for 3 minutes, take it out, wash it, wipe it dry, and observe whether there are cracks or bursts on the appearance of the sample under the light.

[0076]

[0077] Compared with Example 1, Comparative Example 1 removes the annealing heat treatment method, and it can be seen that its strength is significantly reduced, and the corrosion resistance is also slightly reduced. Cracks appeared in the thermal shock resistance in the eighth test. Compared with Example 1, Comparative Example 2 is not doped with aluminum alloy, and its strength is greatly reduced. The corrosion resistance is also greatly reduced, and the thermal shock resistance is similar to that of Comparative Example 1. Compared with Example 1, Comparative Example 3 is doped with Fe but no gradient is set, and the thermal shock resistance and strength are greatly reduced. The corrosion resistance is also slightly reduced but the difference is not large. Compared with Example 1, Comparative Example 4 is not doped with Fe, and its strength and corrosion resistance are greatly reduced, and the thermal shock resistance is also reduced.

Claims

1. A production process for an alumina ceramic sheet, characterized in that: The following steps are involved: S1. Add AlCl3·6H2O to water, stir the solution at room temperature until it is completely dissolved, add ethanol to the solution, and raise the temperature to 65-75°C, then add hexadecyltrimethylammonium bromide while maintaining the temperature, react for 5-10 minutes, then add sodium borohydride to the solution for later use; S2, after the S1 solution becomes transparent, heat it to 85-95°C, maintain it for 20-30 minutes, dry it to obtain a white powder, wash it with water and ethanol, and then dry it for later use; S3, adding FeSO4·6H2O into water, stirring the solution at room temperature to make it uniform, and then adding it to the solution prepared in S1 to obtain solutions with iron contents of 2%, 4% and 6%, respectively. After the solution becomes transparent, the temperature is raised to 90-95°C and maintained for 20-30 minutes. The solution becomes a gel and is dried to obtain a white powder, which is washed with water and ethanol and then dried for later use; S4, the powder obtained in S2, the powder with an iron content of 2% obtained in S3, the powder with an iron content of 4% obtained in S3, and the powder with an iron content of 6% obtained in S3 are successively spread into a mold from bottom to top, and the heating furnace is preheated to 700-750° C., and sintered for 1-1.5 hours to obtain a pre-sintered product; S5, placing the aluminum alloy on the pre-sintered product obtained in S4, and then sending it into the heating furnace again, raising the temperature to 900-950° C., maintaining it for 30-50 minutes, taking it out and cooling it to room temperature; S6. Preheat the heating furnace to 1000-1100°C, send the product obtained in S5 into the heating furnace for sintering for 2-3h, take it out and cool it to room temperature, send it into the heating furnace again, slowly heat it to 600-680°C at a rate of 5°C / min and keep it for 4-5h, then slowly cool it to room temperature at a rate of 5°C / min to obtain alumina ceramics.

2. The production process of alumina ceramic sheet according to claim 1, characterized in that: In step S1, the mass ratio of AlCl3·6H2O, ethanol, hexadecyltrimethylammonium bromide and sodium borohydride is 12:7-8:0.1-0.2:0.1-0.

2.

3. The production process of alumina ceramic sheet according to claim 2, characterized in that: In step S1, the hexadecyltrimethylammonium bromide and sodium borohydride are aqueous solutions with a concentration of 0.02-0.05 g / mL.

4. The production process of the alumina ceramic sheet according to claim 1, characterized in that: In step S4, the mass ratio of the powder obtained in S2, the powder with an iron content of 2% obtained in S3, the powder with an iron content of 4% obtained in S3, and the powder with an iron content of 6% obtained in S3 is 8:2-2.5:0.5-1:0.5-1.

5. The production process of the alumina ceramic sheet according to claim 1, characterized in that: The aluminum alloy is one or more of 5A05, 5052, 5083, and 5005.

6. The production process of the alumina ceramic sheet according to claim 5, characterized in that: The mass ratio of the aluminum alloy in step S5 to the pre-sintered product obtained in step S4 is 3-5:

3.

7. The production process of alumina ceramic sheet according to claim 1, characterized in that: Step S5: The aluminum alloy is pretreated by cleaning with acetone at room temperature and vacuuming at 10 -3 -10 -4 Pa, degas for 1-2h in an environment with a temperature of 120-150℃.

Citation Information

Patent Citations

  • Zinc aluminate luminescent material and preparation method thereof

    CN103849384A

  • Preparation method of mesoporous alumina

    CN104671264A